2014
DOI: 10.1088/0004-637x/796/1/15
|View full text |Cite
|
Sign up to set email alerts
|

Electron Densities and Alkali Atoms in Exoplanet Atmospheres

Abstract: We describe a detailed study on the properties of alkali atoms in extrasolar giant planets, and specifically focus on their role in generating the atmospheric free electron densities, as well as their impact on the transit depth observations. We focus our study on the case of HD 209458 b, and we show that photoionization produces a large electron density in the middle atmosphere that is about two orders of magnitude larger than the density anticipated from thermal ionization. Our purely photochemical calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 98 publications
(155 reference statements)
6
98
1
Order By: Relevance
“…Detailed theoretical models of planetary atmospheres demonstrate that photochemistry cannot explain such different ratios, and drastic changes to atmospheric temperature profiles or clouds are not supported by the data (e.g., Lavvas et al 2014). It is suggested that disk evolution might change the Na/K abundance ratios of the gas that giant planets accrete during formation.…”
Section: Introductionmentioning
confidence: 97%
“…Detailed theoretical models of planetary atmospheres demonstrate that photochemistry cannot explain such different ratios, and drastic changes to atmospheric temperature profiles or clouds are not supported by the data (e.g., Lavvas et al 2014). It is suggested that disk evolution might change the Na/K abundance ratios of the gas that giant planets accrete during formation.…”
Section: Introductionmentioning
confidence: 97%
“…The atmosphere of HD 209458b has been modeled in order to compare to the observed H Lyα, O, Si III , and Na I lines (Fortney et al 2003;Koskinen et al 2013a,b;Lavvas et al 2014). For the purpose of studying the Lyα emission spectrum, Menager et al (2013) calculated the Lyα resonant scattering process in the atmosphere of HD 209458b, based on the atmospheric structure model in Koskinen et al (2013a), and HD 189733b based on an unpublished model (Koskinen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…If only photoelectric heating and line cooling from hydrogen were included, the atmosphere would be hotter by 2000 − 3000 K (Christie et al 2013), giving transit depths far too large in comparison to observations. Furthermore, several studies (García Muñoz 2007;Koskinen et al 2013a;Lavvas et al 2014) suggested that the transition from atomic to molecule hydrogen occurs at pressures P 10 µbar. These studies included detailed heating and cooling physics in the molecular layer.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, χ 2 m (r g = 0) ∼ χ 2 m (r g = 0.1) < χ 2 m (r g = 0.2) < χ 2 m (r g = 0.3), and thus better fits are obtained when the prescribed cloud rests above a poorly reflecting gas atmosphere. Provided that alkalis dominate the gas-phase absorption, this might be consistent with a cloud that lies at pressures less than 10 −4 bar for which the neutral-to-ion alkali transition likely occurs in the atmospheres of close-in giant planets (37).…”
Section: Phase Curve Interpretationmentioning
confidence: 61%